2018
DOI: 10.1101/434993
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Defining the developmental program leading to meiosis in maize

Abstract: In multicellular organisms, the entry into meiosis is a complex process characterized by increasing levels of meiotic specialization. We used single-cell RNA-sequencing to reconstruct the developmental program into meiosis in maize. We observed a smooth continuum of expression stages leading up to meiosis, followed by a sharp reorganization of the transcriptome in early meiotic prophase. This latter transcriptional shift was dramatic, with 26.7% of expressed genes changing by 2 fold or more, and occurred just … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(73 citation statements)
references
References 38 publications
2
71
0
Order By: Relevance
“…Recently, draft manuscripts have been posted online describing additional scRNA-seq results from maize male germinal cells (144 cells; Nelms and Walbot, 2018) and from Arabidopsis roots (3121 cells [Jean-Baptiste et al, 2019] and 4043 cells [Shulse et al, 2018]). It is likely that new technical advances in plant cell isolation and single-cell sequencing methods will emerge to enable single-cell transcriptomics to be applied to more plant organs and species in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, draft manuscripts have been posted online describing additional scRNA-seq results from maize male germinal cells (144 cells; Nelms and Walbot, 2018) and from Arabidopsis roots (3121 cells [Jean-Baptiste et al, 2019] and 4043 cells [Shulse et al, 2018]). It is likely that new technical advances in plant cell isolation and single-cell sequencing methods will emerge to enable single-cell transcriptomics to be applied to more plant organs and species in the future.…”
Section: Discussionmentioning
confidence: 99%
“…During meiosis, chromosomes become increasingly condensed, which may obstruct transcription; in turn, this might lower the necessity for the miRNA machinery. This hypothesis is supported by a recent single-cell sequencing study in maize (Zea mays) meiocytes, which revealed a two-step transcriptome reorganization at early prophase before chromosome condensation (Nelms and Walbot, 2019). During this reorganization, there was downregulation of RNA-mediated translation and gene silencing processes, including those mediated by Ago18a, an AGO1 paralog specifically enriched in the tapetum and meiocytes during meiosis .…”
Section: Discussionmentioning
confidence: 75%
“…To circumvent such low spatiotemporal resolution of bulk analysis, which can be attributed to the crude averaging of various cell types, we performed time-series of scRNA-seq in the VISUAL. Making protoplasts and/or nuclear isolation is the conventional method to perform scRNA-seq in plants [21][22][23] ; however, the protoplast isolation is timeconsuming and potentially stress-inducing, it is not suitable for time-series analysis of the circadian clocks. We therefore obtained total RNA from single cells using glass capillaries in vivo context 24 ( Supplementary Fig.…”
Section: Involvement Of Plant Circadian Clocks In Cell Differentiatiomentioning
confidence: 99%